Decreased Prevalence of Autoimmune Connective Tissue Diseases in Type 1 and Type 2 Diabetes - Abugharbyeh, Aya; Khuder, Sadik; Kahaleh, Bashar (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.